(untitled) (Development Service Industry Management, 2024)
The search for sources of financing for entrepreneurial activity is the importance of ensuring the stable functioning and development of enterprises in modern conditions of economic uncertainty. Taking into account global economic changes, growing competition and challenges related to access to financial resources, the issue of finding and optimal use of various sources of financing becomes extremely relevant for entrepreneurs. This topic becomes especially important in the context of the development of small and medium-sized businesses, which often face limited opportunities to attract capital. Insufficient funding can be a serious obstacle to innovation, expanding markets and increasing competitiveness. In addition, the study of sources of financing of entrepreneurial activities is important for the formation of effective financial management strategies. This allows enterprises not only to provide the necessary resources for current activities, but also to create a financial reserve for future investments and development Finding financing for business development in today’s economy, which is characterized by high competition, rapid technological development and market volatility, creates a number of financial challenges. Therefore, careful analysis and search for traditional and alternative sources of financing, government support programs and international investments will allow to accelerate the efficiency of business development and increase profits. Financing the development of entrepreneurial activity is the subject of scientific research. In modern scientific research, attention is focused on several key aspects of this issue. Ukrainian scientists are also studying the sources of financing entrepreneurial activity. Their works consider the peculiarities of attracting financing in the conditions of the Ukrainian economy, in particular, the difficulty of accessing bank loans, the problems of regulation and the development of alternative sources of financing. For example, Yermak S. O. [1] analyzes the opportunities and challenges associated with the use of leasing and factoring as business financing tools. Hrynkevich S.S., Khuda U.O [2] examines the role of state programs to support entrepreneurship and their impact on access to financial resources. In the works of foreign authors, in particular, the issue of access of enterprises to bank lending, as well as alternative forms of financing, such as venture capital, crowdfunding, and business angels, are widely investigated. For example, research • Johnson highlights the impact of venture capital on the development of startups and emphasizes its importance for innovative industries. O. Blank explores the role of crowdfunding as a new form of fundraising, which is especially relevant for small businesses and startups. The purpose of the research is to find the main sources of financing for the development of entrepreneurial activities, to find state support programs and international investments, and to substantiate the main shortcomings of existing financial sources, as well as to find the most effective approaches to financing activities in adverse economic conditions. Business development in Ukraine is an important component of the country’s economic growth. To achieve success, entrepreneurs need financial resources that can ensure stable development and competitiveness. Ukraine has significant potential for business development due to its strategic location, availability of natural resources, skilled workforce and large domestic market. However, to realize this potential, it is important to ensure access to financial resources. The problem of choosing and optimally using sources of financing is one of the most urgent for modern enterprises. Solving this problem will contribute to improving the financial stability of the business, increasing its competitiveness and ensuring sustainable development in the long term. In this article, we will consider the main sources of financing that can be used for business development in Ukraine. Ukraine offers a wide range of financial opportunities for business development, including traditional and alternative sources of financing, government support programs and international investments. Using these opportunities allows entrepreneurs to attract the necessary capital to implement their projects, promote economic growth and create new jobs. An important condition for successful business development is constant improvement of the investment climate, transparency of regulatory processes, and support for innovation. The use of these opportunities contributes to the creation of innovative products, the expansion of sales markets and the strengthening of the country’s economic potential. It is important to continue reforming the financial sector and create favorable conditions for attracting investments, which will ensure the stable development of business in Ukraine.